Tissue eosinophilia induced by recombinant human interleukin-5 in the hamster cheek pouch membrane - M. Minnicozzi; W. N. Durán; D. Kim; G. J. Gleich; J. Wagner; R. W. Egan (Hindawi Limited, 1995)
Interleukin-5 (IL-5) is a cytokine that preferentially effects the development and function of eosinophils, and is considered important in the pathophysiology of allergic inflammation. In this study, we evaluated the ability of recombinant human IL-5 (rHu IL-5) to promote tissue eosinophilia and the importance of this eosinophilia to pathological alterations in vascular function. Repetitive subcutaneous administration for 18 days of rHu IL-5 resulted in a 7-fold increase in the number of eosinophils found in the ipsilateral hamster cheek pouch membrane. The contralateral cheek pouch membrane and peritoneum of these animals showed lesser but significant elevations in the number of eosinophils. In contrast, denatured rHu IL-5 did not elevate eosinophils in these tissues. Through the use of intravital microscopy and fluorometric analysis, rHu IL-5 treated hamster cheek pouch membranes were evaluated for alterations in microvascular permeability, using plasma clearance of FITC-dextran 150 as an index. Despite promoting a prominent tissue eosinophilia, the repetitive subcutaneous injections of rHu IL-5 did not alter the clearance of FITC-dextran 150. Topical application of rHu IL-5 to the cheek pouch, also, had no effect on the clearance of FITC-dextran 150. Immunofluorescence observations using an antibody to the granule protein, eosinophil peroxidase, indicated that the recruited cells had not degranulated. Our results support the importance of IL-5 in the recruitment of tissue eosinophils, but further stimulation is probably required to cause degranulation of these cells and the ensuing tissue damage.